A study on Perception of Tourists‟ towards Tourism in Ernakulam District - Ninu Rose (International Journal of Scientific Development and Research, 2017)
ndia is a developing country, the government of every states in India are focusing on major areas which will help to accomplish the long term goal of being a Developed country. Among the various areas which contribute towards the economic development, Tourism is one of the emerging sector. Tourism is the act of residing in any place for leisure, business and other purposes. The success of a tourism sector will depend upon the attitude of both domestic and international tourist towards various tourist destinations. The study aims to find out the perception of tourist towards various tourism practices and tourism destination in Ernakulam District. The Kerala is one of the most important state which contributes towards making India the most attractive tourist destination among domestic and international tourists. Ernakulam is one of the most attractive destination in Kerala. Being the most important destination, the study focus on analyzing which factor attracts the tourist towards Ernakulam. I also aims to find out how far the tourist are satisfied with various tourism services and their attitude towards various tourist destinations. The study may also help to point out the suggestions for making improving the tourism sector which will help to boost up this sector. The study reveals that the foreign tourist are greatly attracted towards Ernakulam Tourist destinations and they came to know about various tourist destinations from their friends. It clearly indicates that fame of tourist destinations in Ernakulam are increasing day by day over and above the efforts put forward by promotional techniques. The tourists ‘are greatly attracted by Carnival celebration in Fortkochi and beaches which adds natural beauty. The tourist are highly satisfied with various services provided to them and they prefer typical Kerala foods and nature friendly accommodation facilities.They problem they felt is regarding the matter of cleanliness’, hygiene and safety. But most of them prefer to visit the places in Ernakulam. So government should take few more initiatives to tackles with the problems arising in tourist sector and make it a perfect Tourist Destination.